2014
DOI: 10.1007/s10195-014-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in patients with knee or hip osteoarthritis in a Mediterranean country

Abstract: BackgroundVitamin D plays an important role in bone mineralization, remodeling, and maintenance and therefore its deficiency may be implicated in the pathogenesis of osteoarthritis (OA). Vitamin D status was evaluated in patients with knee or hip OA scheduled for joint replacement. The impact of anthropometric parameters such as gender, age, and body mass index on vitamin D levels was also examined. The study was conducted in a Mediterranean country (Greece).Materials and methodsWe included 164 patients with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
1
40
0
3
Order By: Relevance
“…Furthermore, a meta-analysis of 13 RCTs reported a beneficial effect of vitamin D supplementation (800-100 IU/day) on measures of muscle strength and balance in individuals aged 60 years and older [9]. A metaanalysis of 30 RCTs in individuals of all ages showed a significant positive effect of vitamin D supplementation on muscle strength, which was most evident in people with a 25-hydroxyvitamin D 3 (25[OH]D 3 ) level < 30 nmol/L and in those who were older than 65 years [10]. Vitamin D plays a direct role on muscle quality via activation of the vitamin D receptors, which are involved in muscle protein synthesis and muscle growth [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of 13 RCTs reported a beneficial effect of vitamin D supplementation (800-100 IU/day) on measures of muscle strength and balance in individuals aged 60 years and older [9]. A metaanalysis of 30 RCTs in individuals of all ages showed a significant positive effect of vitamin D supplementation on muscle strength, which was most evident in people with a 25-hydroxyvitamin D 3 (25[OH]D 3 ) level < 30 nmol/L and in those who were older than 65 years [10]. Vitamin D plays a direct role on muscle quality via activation of the vitamin D receptors, which are involved in muscle protein synthesis and muscle growth [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing bone resorption by the elevated levels of parathyroid hormone (PTH) increasing bone turn over, or effect of vitamin D metabolites directly on articular chondrocytes were some of the mechanisms put forwarded to explain the role of vitamin D deficiency in osteoarthritis. 3,6,9,15 Early structural changes in the joints such as defects in cartilage, decrease in volume of cartilage, expansion of sub-chondral bone, and lesions in bone marrow will appear before the onset of clinical symptoms of OA. Reports and observations from earlier studies provided a rationale for the measurement of serum 25-OH vitamin D levels with appearance of knee OA in elderly people and encourage supplementation to raise the serum vitamin D concentration to adequate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Reports and observations from earlier studies provided a rationale for the measurement of serum 25-OH vitamin D levels with appearance of knee OA in elderly people and encourage supplementation to raise the serum vitamin D concentration to adequate levels. [14][15][16] Epidemiological studies showed an association between dietary intake and serum levels of 25-hydroxy vitamin D and the progression of hip 14,15 and knee OA. 12,16 In a recent study, decreased serum level of 25-hydroxy vitamin D was reported in a significant proportion of patients with OA of hip and knee joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future trials will refine the evidence achieved herein. Vitamin D deficiency is found to be associated with the development and progression of osteoarthritis [36], and a relatively high proportion of patients with osteoarthritis of hip or knee are reported to be vitamin D deficient [37][38][39]. However, in large longitudinal epidemiological studies, the Framingham Osteoarthritis Study and the Boston Osteoarthritis of the Knee Study, no relationship was found between the risk of joint space or cartilage loss in knee osteoarthritis, although the risk of worsening osteoarthritis was rather slightly (not statistically significantly) lower in vitamin D deficient persons [40].…”
Section: Important Characteristics Of the Included Studiesmentioning
confidence: 99%